Increasing Functional Leisure Engagement for Children With Autism Using Backward Chaining. Issue 1 (January 2018) - Edwards, Chelsea K.; Landa, Robin K.; Frampton, Sarah E.; Shillingsburg, M. Alice
Research with individuals with disabilities has demonstrated the utility of intervention approaches to address toy play, also referred to as functional leisure engagement (FLE). Examples include prompting FLE, blocking stereotypy, and differentially reinforcing appropriate FLE with social or automatic (i.e., access to stereotypy) reinforcers. Backward chaining has yet to be evaluated, but may be useful for establishing more complex FLE. The current study employed a treatment package consisting of these components with three school-aged children with autism in a therapeutic classroom. Effects were evaluated during pretest and posttest sessions, which consisted of free access to toys in a novel setting. The percentage of session with FLE was evaluated using a multiple probe design across participants. Results showed all participants demonstrated an increase in FLE and two participants showed decreased stereotypy. Feasibility for classroom implementation is discussed.